Morphologic and immunohistochemical features of malignant peripheral nerve sheath tumors and cellular schwannomas - Pekmezci, Melike; Reuss, David; Hirbe, Angela C.; Dahiya, Sonika; Gutmann, David H.; Deimling, Andreas von; Horvai, Andrew E.; Perry, Arie (Modern pathology, 2015)
Cellular schwannoma is an uncommon, but well-recognized, benign peripheral nerve sheath tumor, which can be misdiagnosed as malignant peripheral nerve sheath tumor. To develop consensus diagnostic criteria for cellular schwannoma, we reviewed 115 malignant peripheral nerve sheath tumor and 26 cellular schwannoma cases from two institutions. Clinical data were retrieved from the electronic medical records, and morphologic features, maximal mitotic counts, Ki67 labeling indices, and immunohistochemical profiles (SOX10, SOX2, p75NTR, p16, p53, EGFR, and neurofibromin) were assessed. Several features distinguish cellular schwannoma from malignant peripheral nerve sheath tumor. First, in contrast to patients with malignant peripheral nerve sheath tumor, no metastases or disease-specific deaths were found in patients with cellular schwannoma. More specifically, 5-year progression-free survival rates were 100 and 18%, and 5-year disease-specific survival rates were 100 and 32% for cellular schwannoma and malignant peripheral nerve sheath tumor, respectively. Second, the presence of Schwannian whorls, a peritumoral capsule, subcapsular lymphocytes, macrophage-rich infiltrates, and the absence of fascicles favored the diagnosis of cellular schwannoma, while the presence of perivascular hypercellularity, tumor herniation into vascular lumens, and necrosis favor malignant peripheral nerve sheath tumor. Third, complete loss of SOX10, neurofibromin or p16 expression, or the presence of EGFR immunoreactivity was specific for malignant peripheral nerve sheath tumor (P<0.001 for each). Expression of p75NTR was observed in 80% of malignant peripheral nerve sheath tumors compared with 31% of cellular schwannomas (P<0.001). Fourth, Ki-67 labeling indices ≥20% were highly predictive of malignant peripheral nerve sheath tumor (87% sensitivity and 96% specificity). Taken together, the combinations of these histopathological and immunohistochemical features provide useful criteria to distinguish between malignant peripheral nerve sheath tumor and cellular schwannoma with high sensitivity and specificity. Additional retrospective and prospective multicenter studies with larger data sets will be required to validate these findings.
Published online 5 September 2014
Gesehen am 01.07.2020